Multidrug-resistant Gram-negative bacilli producing oxacillinases and Metallo-β-lactamases isolated from patients in intensive care unit - Annaba hospital - Algeria (2014-2016) - Soumaya Toumi & , Saida Meliani & , Kamel Amoura, Ahmed Rachereche, Mahfoud Djebien, Abdelghani Djahoudi (Journal of Applied Pharmaceutical Science, 2018)
This study aims to investigate the prevalence and genes encoding for carbapenemases of multidrug-resistant Gram-negative bacilli isolated from the intensive care unit in the hospital of Annaba city, Algeria, over a period of 18 months. The isolates were identified using API20E, API 20NE and confirmed by Microscan WalkAway 96. Antimicrobial susceptibility testing was determined by the disk diffusion method according to clinical and laboratory standards institute guidelines. Carbapenemases production was tested using Hodge and imipenem-EDTA Combined Disc tests. Carbapenemases genes were established by Polymerase chain reaction and confirmed by sequencing. 35.52% of 152 isolates were multidrug-resistant. The majority belong to Enterobacteriaceae (75.92%) followed by non-fermentative Gram-negative bacilli (24.07%). The Enterobacteriaceae revealed high resistance to third generation cephalosporin, with the production of cephalosporinases (36.58%) and/or extended-spectrum β-lactamases (34.14%). For non-fermentative Gram-negative bacilli, they showed increased resistance to carbapenems, fluoroquinolones, and aminoglycosides. Fifteen of the MDR strains were resistant to carbapenems, 10 of them were positives for Metallo- β-lactamases and carbapenemases by phenotypic methods. The PCR results showed the presence of blaVIM-2 gene in two Pseudomonas aeruginosa, blaOXA-24 (n = 1), blaOXA-23 (n = 6) and blaNDM-1 (n = 1) in Acinetobacter baumannii. A surveillance of the resistance in this unit is necessary to prevent any therapeutic impasse.
Keywords: Gram-negative bacilli, Metallo-&beta; -lactamases, multidrug resistant, Oxacillinases, Intensive care unit.